2012
DOI: 10.1890/11-1814.1
|View full text |Cite
|
Sign up to set email alerts
|

Why are metapopulations so rare?

Abstract: Roughly 40 years after its introduction, the metapopulation concept is central to population ecology. The notion that local populations and their dynamics may be coupled by dispersal is without any doubt of great importance for our understanding of population‐level processes. A metapopulation describes a set of subpopulations linked by (rare) dispersal events in a dynamic equilibrium of extinctions and recolonizations. In the large body of literature that has accumulated, the term “metapopulation” is often use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 85 publications
2
95
0
1
Order By: Relevance
“…Movement patterns along the mountain ridge of over 30 km underline the possibility that individual birds may move between all subpopulations and, hence, maintain gene flow across the entire landscape (up to 85 km). In contrast, populations in the Black Forest (Braunisch et al 2010) and Bavarian Alps (Segelbacher et al 2003a, b) revealed signatures for spatial structure at scales of only 10 km (Sachot et al 2006;Storch 1993Storch , 1995Storch and Segelbacher 2000; but see Fronhofer et al 2012;Segelbacher et al 2008). In the Bavarian Alps, the highly fragmented landscape with unsuitable farmland and pastures between subpopulations is regarded as the main reason for the genetic isolation (Segelbacher et al 2003a, b;.…”
Section: Spatial and Genetic Population Structurementioning
confidence: 99%
“…Movement patterns along the mountain ridge of over 30 km underline the possibility that individual birds may move between all subpopulations and, hence, maintain gene flow across the entire landscape (up to 85 km). In contrast, populations in the Black Forest (Braunisch et al 2010) and Bavarian Alps (Segelbacher et al 2003a, b) revealed signatures for spatial structure at scales of only 10 km (Sachot et al 2006;Storch 1993Storch , 1995Storch and Segelbacher 2000; but see Fronhofer et al 2012;Segelbacher et al 2008). In the Bavarian Alps, the highly fragmented landscape with unsuitable farmland and pastures between subpopulations is regarded as the main reason for the genetic isolation (Segelbacher et al 2003a, b;.…”
Section: Spatial and Genetic Population Structurementioning
confidence: 99%
“…True metapopulations carry high extinction risks for individual patches and are relatively uncommon in nature; however, the term usefully describes many spatially structured populations (Fronhofer et al 2012). The consideration of genetically connected populations as metapopulations and the promotion of functional connectivity among habitat patches are important for conserving populations scattered among, or restricted to, isolated habitat patches (Wahlberg et al 1996, Gibbs 2000, Wiens 2002.…”
Section: Introductionmentioning
confidence: 99%
“…To guide our analyses, we conceived of rats in the Falklands as a metapopulation in which island sub-populations are linked by dispersal, and in which the presence of rats is determined by the balance between colonization and extinction among islands (Fronhoffer et al 2012). Following this classical view of metapopulations (Levins 1969(Levins , 1970, we hypothesized that the presence of rats would decrease with distance from the nearest island with rats, the island presumably functioning as a reservoir and source of rats (for the purposes of this manuscript, we use "source" to describe any island on which rats are present).…”
mentioning
confidence: 99%